Habitat structure influences the song characteristics within a population of Great Tits Parus major. Issue 3 (2nd July 2016) - Bueno-Enciso, Javier; Ferrer, Esperanza S.; Barrientos, Rafael; Sanz, Juan José
ABSTRACT: Capsule: The structure of Great Tit Parus major songs is shaped by the acoustic properties of the habitat within the breeding territory of individuals. Aim: To test whether the structure of the habitat influences song structure within a population of Great Tits P. major . Methods: We recorded Great Tit songs from 42 territories on two different days and measured the habitat structure in each territory. We also trapped the males and estimated the breeding density around each territory, so were able to control the analysis by date, breeding density and male characteristics. Results: Song pause length was positively affected by the ground cover, while the song rate and the minimum frequency were negatively affected by the shrub cover. Male size negatively affected the peak frequency of the songs, whereas the age of the males affected the frequency range; older males sang with a broader bandwidth. Conclusion: This study suggests that Great Tits are capable of adjusting their vocalizations in each territory, presumably to enhance transmission owing to vocal plasticity.